Admission haemoglobin and albumin as correlates of central nervous system inflammation in rhodesiense human African trypanosomiasis at Rumphi District Hospital, Malawi - Westain T. Nyirenda; Lovemore Mapahla; Bonheur Dounebaine; Nebiyu Dereje; Peter S. Nyasulu (Journal of Public Health in Africa, 2026)
Background: Rhodesiense human African trypanosomiasis (rHAT) is an acute zoonotic infection that can rapidly progress to central nervous system (CNS) disease. As lumbar puncture is no longer routinely required for treatment selection, district hospitals need accessible measures associated with CNS inflammatory burden. Aim: This study aimed to evaluate routine admission clinical and laboratory measures as correlates of cerebrospinal-fluid white-cell count and to describe changes in this count during early hospital care. Setting: The study was conducted at Rumphi District Hospital, a public secondary-level treatment facility serving rural communities in the Vwaza Marsh focus of northern Malawi. Methods: We retrospectively studied patients aged ≥ 6 years with parasitological confirmed rHAT from 2012–2024. Cerebrospinal-fluid white-cell counts at admission and Day 11 were analysed using mixed-effects negative binomial regression, reporting adjusted incidence rate ratios (aIRRs) with 95% confidence intervals (CIs). Results: Forty-three patients met the eligibility criteria; 43 contributed admission counts, and 42 contributed Day-11 counts. Day-11 cerebrospinal-fluid white-cell counts were 75% lower than admission counts (aIRR = 0.25, 95% CI: 0.14–0.45; p < 0.001). Stage 2 disease was associated with a higher count than Stage 1 disease (aIRR = 4.23, 95% CI: 1.35–13.30; p = 0.013). Each 1 g/dL increase in haemoglobin and albumin was associated with lower expected counts (haemoglobin aIRR = 0.83, 95% CI: 0.78–0.89; p < 0.001; albumin aIRR = 0.70, 95% CI: 0.54–0.92; p = 0. 009). Conclusion: Lower haemoglobin and albumin were associated with greater cerebrospinal-fluid inflammation, which declined during early care. As accessible admission measures, they may support recognition, triage and monitoring of CNS burden in rHAT, pending prospective diagnostic-accuracy validation before implementation. Contribution: This study links routine blood measures to cerebrospinal-fluid inflammation in rHAT, informing prospective validation priorities.